IgE-mediated sensitizations to Blomia tropicalis allergens in Malaysian allergic population - Olajide, Abosede Temitope; Ismail, Intan Hakimah; Zakaria, Atiqah Farah; Abdullah, Noormalin; Mohammad, Nik Mohd Yunus; Tan, Andrew Kie Kion; Ramli, Rosdi; Othman, Filla Dalila; Amiruddin, Salman; Jacquet, Alain; Tham, Chau Ling (Nature Research, 2025)
Allergic sensitizations to Dermatophagoides pteronyssinus and Dermatophagoides farinae house dust mite (HDM) species are continuously on the rise in Asian countries. Whereas the role of Blomia tropicalis, a mite species widely distributed in South/Southeast Asia, in the development of allergic diseases is well evidenced, the association between Blomia sensitizations and allergic symptoms remains poorly investigated in Malaysia. This cross-sectional study characterized the prevalence of sensitization to the clinically relevant Blomia tropicalis mite in cohorts of 329 subjects from the Klang Valley or East Coast Malaysia and developing allergic symptoms. Total specific IgE to Blomia was assayed by ImmunoCAP, IgE reactivities to recombinant Blo t 2, 5, 7, 21 were determined by ELISA IgE assays, and the association of allergic sensitization with clinical allergic symptoms was further investigated. 55% of the population was sensitized to Blo t, and sensitization to rBlo t 2, 5, 7, and 21 reached 56.9%, 74.6%, 83.4% and 57.5% respectively. rBlo t allergens sensitization was a risk factor for the development of allergic diseases, and high odds ratios observed with AA and AR indicate a strong predictive value for the diagnosis of these allergic diseases (p < 0.05). Higher rBlo t sensitization rates were observed in Klang Valley allergic patients compared to the East Coast (p < 0.05). Our study showed that Blomia sensitizations represent risk factors of allergic diseases in different regions of Malaysia, and Blo t 5 and Blo t 21, Blo t 2 and Blo t 7 can represent major Blomia allergens.